2017
DOI: 10.3390/su9040606
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated with High Ambient Temperatures, Heatwaves, and the Urban Heat Island in Athens, Greece

Abstract: Climate change looms as the biggest threat of the 21st century, and its effect on urban mortality is exacerbated by urban heat islands. This study analyzes the impact of high temperatures, heatwaves, and the urban heat island on the cardiovascular and respiratory mortality of people over 65 years of age for the years 2002 to 2012. The area of application is Athens, Greece, an urban agglomeration experiencing an urban heat island of high intensity. The correlation of the daily cardiovascular and respiratory mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 62 publications
(71 reference statements)
0
36
0
5
Order By: Relevance
“…The synergy of the UHI and the global climate change ( Figure 14) will further exacerbate the existing overheating hazards in Athens. Increased energy for cooling is expected to outweigh the decreased heating consumption for Greece [150,151] and exert additional stress on current UHI health implications in Athens [152].…”
Section: Discussionmentioning
confidence: 99%
“…The synergy of the UHI and the global climate change ( Figure 14) will further exacerbate the existing overheating hazards in Athens. Increased energy for cooling is expected to outweigh the decreased heating consumption for Greece [150,151] and exert additional stress on current UHI health implications in Athens [152].…”
Section: Discussionmentioning
confidence: 99%
“…The increase of temperature may be attributed to the influence of the radiative properties of urban surfaces and the three-dimensional configuration and heat capacity of buildings [1][2][3][4][5][6]. In response to the increased urban (air and land surface) temperatures and the strong relationship between high urban air temperatures and adverse heat-related health outcomes (e.g., thermal discomfort, mortality, and heat-related illness) [7][8][9][10][11][12], urban planners and decision makers are recognizing the growing need to create more attractive, thermally comfortable, and sustainable cities, especially as urban populations expand and climatic variability and extremes increase [13][14][15]. Results of specific building adaptation studies for Athens, Greece showed that this is possible when appropriate and energy-efficient building technologies are used [16].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic heat release from transport and the heating-cooling systems of the buildings further exacerbate the phenomenon [18][19][20]. Both UHI and SUHI can be detected throughout the year, but they are of particular public policy concern during the summer, because higher surface and air temperatures are associated with increases in electricity demand for air conditioning, air pollution, and heat stress-related mortality and illness [21][22][23][24][25]. Several SUHI studies have been performed in the Mediterranean area, most of them revealing that higher UHI intensities are found in the summer period [13,[26][27][28][29][30].Land surface temperature is a controlling factor for most of the physical, chemical and biological processes on the earth, and can be considered as a measure of climate change [31][32][33][34].…”
mentioning
confidence: 99%